Time series econometric estimation of supply equation for Malaysian rice sector - Umar, Haruna Suleiman; Abdullah, Amin Mahir; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin (Asian Economic and Social Society, 2014)
Rice production in the country is characterized by two production seasons namely, main- season and off-season. Officially, the two production seasons data usually aggregated to form single data of domestic rice supply for the nation. This aggregation is refers to as all-season rice production. All the previous studies estimated supply equation based on the aggregated data thereby denying the opportunity of having a comprehensive insight into the structural relationship exist in the off-and-main season?s rice production necessary for holistic policy analysis and decision. Hence, this study attempted estimating supply equation by disaggregation into main-season, off-season, and all-seasons? rice production equations. Time series data (1980-2012) were collected and analyzed using both co-integration and non-co-integration approaches. For valid inference, estimated coefficients were subjected to autocorrelation, heteroskedasticity, misspefication and structural stability diagnostic-tests. The results show that estimated coefficients for main-season and off-season paddy production equations exhibited common characteristics in terms of economic and statistical properties. Therefore, the estimated coefficients for all-season paddy production, which represents the aggregate information of main and off- season?s paddy production, could still be adopted to explain relationship in supply side of the rice sector.